The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1749-8198.2010.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ground‐based Radar for Climate‐Scale Studies of Weather and Rainfall

Abstract: Reflectivity data from weather radar provide information on the location and quantity of water and ice in the atmosphere at high spatial and temporal resolutions. Although the analysis of radar data facilitates spatially accurate climatologies of weather events and rainfall, relatively few studies have utilized data from the US Next Generation Radar (NEXRAD) network for climate‐scale research. Towards the goal of increasing the use of these data by geographers, this article details the collection of radar data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 155 publications
(305 reference statements)
0
16
0
Order By: Relevance
“…In grid cells where multiple reflectivity values are available, we performed several experiments and determined that using the highest value from those available is the best solution, as we found that employing a weighted average algorithm leads to a low bias. This may be due to the fact that some stations have a slightly weaker signal [57]. Cells with missing values are filled using the Cressman interpolation [58].…”
Section: Methodsmentioning
confidence: 99%
“…In grid cells where multiple reflectivity values are available, we performed several experiments and determined that using the highest value from those available is the best solution, as we found that employing a weighted average algorithm leads to a low bias. This may be due to the fact that some stations have a slightly weaker signal [57]. Cells with missing values are filled using the Cressman interpolation [58].…”
Section: Methodsmentioning
confidence: 99%
“…Overeem et al (2009) derived a 10-year climatology of radar-based rainfall for climatological and hydrological applications. Matyas (2010) has further emphasized the importance of weather radar for such applications. Germann et al (2006) have provided solutions using radars to study orographic precipitation in a rather difficult mountainous region of the Swiss Alps.…”
Section: A Devasthale and L Norin: Radar Observations Of Precipitatmentioning
confidence: 99%
“…Three radar systems have been deployed along the Tuscan coastal area. Due to the compact size (90 × 130 cm 2 ) and limited weight (about 100 kg), the system can be installed almost everywhere and the installation requirements are practically reduced based on the availability of electric power (the consumption is less than 300 W on average) and the connectivity for data transfer. The radar transmitter is based on a magnetron cavity and on a solid-state modulator.…”
Section: Set Up Of the Radar Systemsmentioning
confidence: 99%
“…Undoubtedly, weather radars are among the most relevant tools for accurately monitoring precipitation events, therefore they are a key instrument for the development of nowcasting and early warning systems. In addition, radar systems have been and still are an indispensable tool for observing weather and increasing the knowledge on precipitation dynamics and hydrometeor statistics [1][2][3][4], subjects of primary interest both in meteorology and in climatology.…”
Section: Introductionmentioning
confidence: 99%